Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's determine which function is equivalent to the given expression [tex]\( y = x^2 - 10x + 9 \)[/tex].
Below are the options we need to verify:
1. [tex]\( y = (x + 5)^2 + 16 \)[/tex]
2. [tex]\( y = (x - 5)^2 + 16 \)[/tex]
3. [tex]\( y = (x + 5)^2 - 16 \)[/tex]
4. [tex]\( y = (x - 5)^2 - 16 \)[/tex]
To verify equivalence, we will simplify each option and compare it to the given expression.
1. Option 1: [tex]\((x + 5)^2 + 16\)[/tex]
[tex]\[ (x + 5)^2 + 16 = (x^2 + 10x + 25) + 16 = x^2 + 10x + 41 \][/tex]
Clearly, [tex]\(x^2 + 10x + 41\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
2. Option 2: [tex]\((x - 5)^2 + 16\)[/tex]
[tex]\[ (x - 5)^2 + 16 = (x^2 - 10x + 25) + 16 = x^2 - 10x + 41 \][/tex]
Clearly, [tex]\(x^2 - 10x + 41\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
3. Option 3: [tex]\((x + 5)^2 - 16\)[/tex]
[tex]\[ (x + 5)^2 - 16 = (x^2 + 10x + 25) - 16 = x^2 + 10x + 9 \][/tex]
Clearly, [tex]\(x^2 + 10x + 9\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
4. Option 4: [tex]\((x - 5)^2 - 16\)[/tex]
[tex]\[ (x - 5)^2 - 16 = (x^2 - 10x + 25) - 16 = x^2 - 10x + 9 \][/tex]
This simplifies to [tex]\(x^2 - 10x + 9\)[/tex], which is exactly the given expression.
Thus, the expression that is equivalent to [tex]\( y = x^2 - 10x + 9 \)[/tex] is:
[tex]\[ y = (x - 5)^2 - 16 \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{4} \][/tex]
Below are the options we need to verify:
1. [tex]\( y = (x + 5)^2 + 16 \)[/tex]
2. [tex]\( y = (x - 5)^2 + 16 \)[/tex]
3. [tex]\( y = (x + 5)^2 - 16 \)[/tex]
4. [tex]\( y = (x - 5)^2 - 16 \)[/tex]
To verify equivalence, we will simplify each option and compare it to the given expression.
1. Option 1: [tex]\((x + 5)^2 + 16\)[/tex]
[tex]\[ (x + 5)^2 + 16 = (x^2 + 10x + 25) + 16 = x^2 + 10x + 41 \][/tex]
Clearly, [tex]\(x^2 + 10x + 41\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
2. Option 2: [tex]\((x - 5)^2 + 16\)[/tex]
[tex]\[ (x - 5)^2 + 16 = (x^2 - 10x + 25) + 16 = x^2 - 10x + 41 \][/tex]
Clearly, [tex]\(x^2 - 10x + 41\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
3. Option 3: [tex]\((x + 5)^2 - 16\)[/tex]
[tex]\[ (x + 5)^2 - 16 = (x^2 + 10x + 25) - 16 = x^2 + 10x + 9 \][/tex]
Clearly, [tex]\(x^2 + 10x + 9\)[/tex] is not equivalent to [tex]\(x^2 - 10x + 9\)[/tex].
4. Option 4: [tex]\((x - 5)^2 - 16\)[/tex]
[tex]\[ (x - 5)^2 - 16 = (x^2 - 10x + 25) - 16 = x^2 - 10x + 9 \][/tex]
This simplifies to [tex]\(x^2 - 10x + 9\)[/tex], which is exactly the given expression.
Thus, the expression that is equivalent to [tex]\( y = x^2 - 10x + 9 \)[/tex] is:
[tex]\[ y = (x - 5)^2 - 16 \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{4} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.